2009
DOI: 10.1002/adma.200803564
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D Photonic Crystals of Ellipsoids: Convective Self‐Assembly in Magnetic Field

Abstract: In photonic crystals, two materials with different refractive indexes alternate with a specific periodicity on the opticalwavelength scale. Analogous to the band-gap for electrons in semiconductors, the spatially periodic structure in photonic crystals results in a forbidden stop-band for a particular spectral range of photons, the so-called photonic band-gap. Since being first proposed by Yablonovich and John, [1,2] photonic crystals have been desired to give complete photonic band-gap in the optical regime. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
209
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(210 citation statements)
references
References 19 publications
1
209
0
Order By: Relevance
“…Synthetic fabrication of photonic crystal systems is well advanced [35][36][37][38][39] with many self-assembly processes emerging as an exciting hot-topic currently [40,41]. However, with few exceptions [7], it is only highly ordered 3D systems that have been fabricated for the visible band.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic fabrication of photonic crystal systems is well advanced [35][36][37][38][39] with many self-assembly processes emerging as an exciting hot-topic currently [40,41]. However, with few exceptions [7], it is only highly ordered 3D systems that have been fabricated for the visible band.…”
Section: Resultsmentioning
confidence: 99%
“…Random DBRs are frequently examined and used as optical components such as filters, microcavities and waveguides, where broadband optical reflection can be advantageous [7], and understanding this kind of biological system could lead to inspiration for spindlebased three-dimensional angle-independent broadband reflectors (e.g. ellipsoidal three-dimensional photonic crystals [8]). …”
Section: Introductionmentioning
confidence: 99%
“…[526] In a similar fashion, Ding et al recently demonstrated a method using external magnetic fields to create photonic crystals (see Section 6.1) by organizing a population of sub-micrometer-length magnetic ellipsoids. [527] The researchers were able to control the color of the resulting ellipsoidal superlattice simply by changing the size of the ellipsoids.…”
Section: Insect-built Materials and Structuresmentioning
confidence: 99%